2021
DOI: 10.1002/adsc.202100473
|View full text |Cite
|
Sign up to set email alerts
|

State of the Art in Crystallization‐Induced Diastereomer Transformations

Abstract: Crystallization-induced diastereomer transformations (CIDT) enable isolation of the target compounds in high enantio-and diastereomeric purities and with up to quantitative yields simply by filtration. Numerous inspiring examples of this appealing synthetic strategy reported over the last fifteen years are reviewed. Important observations along with aspects to consider when designing CIDT experiments are discussed. 3.3. Formation of Schiff Base or Related Intermediates 3.4. Aza-Michael and Mannich-Type Reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 220 publications
(273 reference statements)
0
37
1
1
Order By: Relevance
“…CIDT reactions featuring aza-Michael additions to 3-acylacrylic acids have proven to provide a straightforward access to diversely functionalized α-amino acids in a highly stereoselective fashion (for reviews, see Kolarovic ˇand Jakubec. 9 Recent examples: Siv ak et al 24 and Valachov a et al 25 For a cognate Mannich-type system, see Marc ˇekov a et al 26 Examples of CIDT in aza-Michael additions to other substrates: Bravo et al 27 and Amara et al 28 ). The syntheses are not sensitive to air or moisture and typically proceed at ambient or close to ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CIDT reactions featuring aza-Michael additions to 3-acylacrylic acids have proven to provide a straightforward access to diversely functionalized α-amino acids in a highly stereoselective fashion (for reviews, see Kolarovic ˇand Jakubec. 9 Recent examples: Siv ak et al 24 and Valachov a et al 25 For a cognate Mannich-type system, see Marc ˇekov a et al 26 Examples of CIDT in aza-Michael additions to other substrates: Bravo et al 27 and Amara et al 28 ). The syntheses are not sensitive to air or moisture and typically proceed at ambient or close to ambient temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…However, on the other side of the coin, both the stereochemical outcome and occurrence of CIDT itself still remain challenging to plan or predict due to numerous interrelated factors that can possibly influence the final result (for an example of a seemingly suitable aza‐Michael substrate, which failed to deliver CIDT, see Sivák et al 19 Additional references can be found in Kolarovič and Jakubec 9 ). It is presumable that these circumstances constitute a major cause why CIDT, otherwise considered to be a “dream reaction” on an industrial scale, 20 has not found more widespread use in stereoselective synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reactions that generate stereoisomeric mixtures, simple recrystallizations cannot overcome the fact that valuable material will be lost as undesired stereoisomers; however, for cases in which equilibration between stereoisomers is mechanistically feasible, convergence to a single stereoisomer of the product can be achieved by engineering crystallization-induced diastereomer transformations (CIDTs). CIDTs are highly desirable in synthetic chemistry and industrial applications because they provide a means to generate highly stereoenriched products without requiring additional tedious purifications ( 12 , 13 ). CIDT selectivity is governed by crystallization thermodynamics: Diastereomers undergoing CIDT contain one or more static asymmetric centers and at least (and commonly) one labile element of chirality that is subjected to equilibration.…”
mentioning
confidence: 99%
“…Implementation of CIDT strategies into synthetic routes reduces the effort required to access a single stereoisomer of a complex molecule: 100% theoretical yield of a single stereoisomeric product can be obtained from an initial mixture of interconverting epimers. CIDT reactions are usually applied to specific problems in industrial chemistry, they are difficult to predict, and generalizable non-auxiliary–based CIDT methods are currently underdeveloped ( 12 , 13 ). We were interested in testing the notion that by leveraging epimerization to achieve stereoconvergence in complex systems, we could accrue unique advantages through the merged application of asymmetric catalysis and crystallization-driven selectivity.…”
mentioning
confidence: 99%